2015
DOI: 10.1585/pfr.10.1402056
|View full text |Cite
|
Sign up to set email alerts
|

Creation of Impurity Source inside Plasmas with Various Types of Tracer-Encapsulated Solid Pellet

Abstract: A Tracer-Encapsulated Solid Pellet (TESPEL) was developed for promoting an impurity transport study in a magnetically-confined plasma. One of the advantages of the TESPEL is that it can make a three-dimensionally localized impurity source in the plasma. This enables us to inject the tracer impurity inside or in the vicinity of the region of interest. Recently, a new-type TESPEL with a thinner outer shell has been developed in order to achieve a shallower deposition of the tracer impurity. With the TESPEL havin… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
4
0

Year Published

2016
2016
2023
2023

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 8 publications
(4 citation statements)
references
References 23 publications
0
4
0
Order By: Relevance
“…From past experience with such polystyrene shells, and to be on the safe side, the polystyrene shell with an outer diameter of 900 μm and an inner core diameter of 660 μm (the shell thickness being 120 μm) is currently under development. Compared with the thick-shell-type TESPEL 24 having the outer diameter of 900 μm and the inner core diameter of 300 μm, i.e., a shell thickness of 300 μm (used in the proof-ofprinciple experiment), the TESPEL payload capacity will increase approximately tenfold. Therefore, based on the results of the second test of the proof-of-principle experiment, a single TESPEL containing a sufficient amount of the inorganic compound impurity tracer will be applicable in the very near future.…”
Section: Discussionmentioning
confidence: 99%
“…From past experience with such polystyrene shells, and to be on the safe side, the polystyrene shell with an outer diameter of 900 μm and an inner core diameter of 660 μm (the shell thickness being 120 μm) is currently under development. Compared with the thick-shell-type TESPEL 24 having the outer diameter of 900 μm and the inner core diameter of 300 μm, i.e., a shell thickness of 300 μm (used in the proof-ofprinciple experiment), the TESPEL payload capacity will increase approximately tenfold. Therefore, based on the results of the second test of the proof-of-principle experiment, a single TESPEL containing a sufficient amount of the inorganic compound impurity tracer will be applicable in the very near future.…”
Section: Discussionmentioning
confidence: 99%
“…Core-shell spheres have also been developed and adopted in MF applications-see two examples shown in figure 10. Small hollow pellets are excellent tools for the calibration of spectroscopic diagnostics in tokamaks and stellarators like LHD [9,39], as a well-known quantity of the desired mat erial can be delivered to the plasma core. The shell protects the core material from ablation and loss in the launch tube and plasma edge region and ensures that the desired quantity of mat erial to be studied reaches the core.…”
Section: Existing Optionsmentioning
confidence: 99%
“…Preliminary results showed that the edge flow structure is oscillated in the condition near the density threshold of transition and turbulence intensity is related with the flow, but it is changed during the oscillatory phase. Solitary and mono-cycle shaped flow structure appears by the small pellet (TESPEL [51]) injection in which the local potential change travels towards the core with two different time scales and the sign of flow velocity in the edge region changes abruptly.…”
Section: Flow Structuresmentioning
confidence: 99%